2013
DOI: 10.1111/jne.12055
|View full text |Cite
|
Sign up to set email alerts
|

Recent Evidence for Rapid Synthesis and Action of Oestrogens During Auditory Processing in a Songbird

Abstract: It is now clear that estrogens are not just circulating reproductive hormones, but that they also have neurotransmitter-like properties in a wide range of brain circuits. The view of estrogens as intrinsic neuromodulators that shape behavior has been bolstered by a series of recent developments from multiple vertebrate model systems. Here, we review several recent findings from studies of songbirds showing how the identified neural circuits that govern auditory processing and sensorimotor integration are modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 143 publications
(183 reference statements)
0
23
0
Order By: Relevance
“…This approach is often limited by the low concentration of compounds recovered in the dialysates and the limited sensitivity of the assays. However, it was reported that this approach allowed quantifying dynamic changes in E 2 concentration taking place in auditory brain areas of zebra finches during social interactions and this initiated an entire line of research . We recently showed that changes in E 2 concentrations can similarly be detected in the POA of Japanese quail during sexual interactions by ultrasensitive RIA based on an iodinated ligand .…”
Section: Discussionmentioning
confidence: 99%
“…This approach is often limited by the low concentration of compounds recovered in the dialysates and the limited sensitivity of the assays. However, it was reported that this approach allowed quantifying dynamic changes in E 2 concentration taking place in auditory brain areas of zebra finches during social interactions and this initiated an entire line of research . We recently showed that changes in E 2 concentrations can similarly be detected in the POA of Japanese quail during sexual interactions by ultrasensitive RIA based on an iodinated ligand .…”
Section: Discussionmentioning
confidence: 99%
“…During social interactions, neurochemical systems that respond to social stimuli can serve a potent adaptive function by matching sensory physiology to the signals of a social partner (e.g., Castelino and Schmidt 2010;Remage-Healey et al 2013). The current study investigated sensory physiology in male mice paired with female social partners, comparing the mean serotonergic activity measured in males was negatively correlated with the number of broadband squeaks emitted by the female partner.…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences have not been found for either receptor expression in NCM. Selective agonists for both classical receptors have not been able to reproduce the rapid auditory evoked effects of E2 (Remage-Healey et al , 2013), suggesting that other membrane receptors (ex: GPER1 or ER-X) could control this signaling. GPER1 expression is sexually dimorphic in zebra finch telencephalon around the critical period of song-learning; however, this sex differences disappears by adulthood (Acharya & Veney, 2012).…”
Section: The Zebra Finch Model Systemmentioning
confidence: 99%